REVIEW MINERAL KRITIS GLOBAL DAN TANTANGAN EKSPLORASINYA DI INDONESIA - Rizal, Khairu; Nurkhamim; Idrus, Arifudin (Indonesian Mining Journal, 2024)
Global critical minerals will highlight critical minerals such as lithium, cobalt, rare earth elements (REEs) and nickel that are critical in the clean energy transition. The analysis also covers the distribution of critical minerals in different regions of the world, including Europe, Africa, the Middle East, and Asia. It also discusses challenges in the extraction and processing of critical minerals and implications for sustainable exploration practices. The method used was a literature review of journals. The results show that countries such as Australia, the Democratic Republic of Congo, and China have significant critical mineral reserves. However, the African continent also has great potential in providing critical minerals needed for the clean energy transition. Therefore, emphasizing the importance of securing a reliable supply of critical minerals to support industrial and technological ambitions. In conclusion, then, with Australia, China, and Africa as major providers of clean energy, the provision of critical minerals such as nickel, lithium, cobalt, and REEs is essential for the clean energy transition and to control processes and reduce production costs, improve geological data and laboratory facilities for analysis are required. Indonesia has significant reserves for the global transition to clean energy and technological advancement. Hence, it is strategically positioned in the global mineral market as it becomes a focal point for geopolitical competition, especially between major powers. The regulatory framework in Indonesia can be complex and can pose challenges for foreign investment to enter, so addressing these challenges through increased research and regulatory alignment will be critical to unlocking Indonesia's abundant REE resources and meeting global demand.